1974
DOI: 10.1038/bjc.1974.66
|View full text |Cite
|
Sign up to set email alerts
|

Breast Volumes in Cancer of the Breast

Abstract: A method has been devised to calculate breast volumes from mammograms. This has been applied to mammograms from 42 women with breast cancer and 42 age-matched normal controls. No difference in breast volumes was noted. Images Fig. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 2 publications
3
68
0
Order By: Relevance
“…Thurfjell et al 20 assigned subjective size categories according to the area covered by the breast on mammographic film, and Senie et al 7 determined total breast area by use of a planimeter applied to caudal projections of mammograms, but no association was found in these studies using mammogram-based measurements of breast size. However, Scutt et al 21 and Kato et al, 22 using the same methods as Katariya et al, 19 demonstrated positive associations between breast size and breast cancer risk. By using patient and physician reported subjective breast size classifications, no association was seen in Caucasian American women, 23 but a positive association was seen in a population of Japanese women.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thurfjell et al 20 assigned subjective size categories according to the area covered by the breast on mammographic film, and Senie et al 7 determined total breast area by use of a planimeter applied to caudal projections of mammograms, but no association was found in these studies using mammogram-based measurements of breast size. However, Scutt et al 21 and Kato et al, 22 using the same methods as Katariya et al, 19 demonstrated positive associations between breast size and breast cancer risk. By using patient and physician reported subjective breast size classifications, no association was seen in Caucasian American women, 23 but a positive association was seen in a population of Japanese women.…”
Section: Discussionmentioning
confidence: 92%
“…Katariya et al 19 geometrically calculated the volume of the breast based on mammographic measurements. Thurfjell et al 20 assigned subjective size categories according to the area covered by the breast on mammographic film, and Senie et al 7 determined total breast area by use of a planimeter applied to caudal projections of mammograms, but no association was found in these studies using mammogram-based measurements of breast size.…”
Section: Discussionmentioning
confidence: 99%
“…Breast size as reflecting the amount of glandular target tissue may in itself be an important risk factor for breast cancer [9] though most of what determines total breast size seems to relate to the amount of fat in the breast [10]. This might explain why no differences in total breast volume between women with and without breast cancer could be found [11].…”
Section: Discussionmentioning
confidence: 99%
“…Katariya et al considered breast as a cone and used the formula of calculation of the volume of a cone as shown in figure by following formula [10] :…”
Section: Discussionmentioning
confidence: 99%